Co-extruded wheat/okra composite blends result in soft, cohesive and resilient crumbs rich in health-promoting compounds. (1st December 2021) - Xu, Kang; Debelo, Hawi; Roman, Laura; Guo, Mengmeng; Ferruzzi, Mario G.; Martinez, Mario M.
Highlights: Extrusion of okra raised the content of soluble dietary fiber and free and bound phenolic acids. Epigallocatechin was highly susceptible to thermal degradation during screw extrusion. A small portion of free quercetin-3-O-glucoside was found as bound after screw extrusion. Extruded wheat flour-extruded okra flour blend resulted in elastic and cohesive crumbs. Abstract: This work investigates the partial solubilization of cell wall polysaccharides in okra flours and the changes in the profile of free and bound phenolics through twin-screw extrusion. The comparison between extruded wheat flour-native okra flour (EWF-OF) and extruded wheat flour-extruded okra flour (EWF-EOF) composite blends revealed that extrusion led to an increase of soluble dietary fiber from 7.76 to 10.02 g/100 g. Extrusion of okra also resulted in a significant increase of free and bound phenolic acids, the latter consisting mostly of ferulic acid, as well as the thermal degradation of free epigallocatechin, and the binding of a small portion of quercetin-3- O -glucoside likely to a carbohydrate fraction. Bread crumbs from EWF-EOF (at 15% replacement level) exhibited a significantly lower hardness and higher elasticity, cohesiveness and resilience (from 28.28 N, 0.94, 0.49 and 0.17 to 7.54 N, 0.99, 0.70 and 0.35, respectively), which closely resembled the textural attributes of wheat bread.